Monoclonal antibodies that define neutralizing epitopes of pertussis toxin: conformational dependence and epitope mapping. - Lang, A B (1989)
The epitope specificities of 13 hybridomas secreting monoclonal antibodies (MAbs) specific for pertussis toxin (PT) is described. Hybridoma lines were derived by the fusion of spleen cells from mice immunized with native PT, Formalin-detoxified PT, or isolated PT subunits (S1 to S5) with the myeloma line X63-Ag8.653. Five MAbs showed a toxin-neutralizing ability, which was demonstrated by use of a Chinese hamster ovary cell assay system and by a NAD glycohydrolase assay. All five toxin-neutralizing MAbs demonstrated high specificities for and reactivities with native PT but were unable to bind to denatured PT. One MAb was able to neutralize the enzymatic activity of PT. The other four neutralizing MAbs inhibited the binding of PT or PT subunits to the surface of Chinese hamster ovary cells, as shown by an immunofluorescence assay. All neutralizing MAbs reacted with purified S2-S4 or S3-S4 dimers but not with S4 alone. Three MAbs which recognized a common epitope shared by S2 and S3 (which are about 70% homologous at the DNA level) and one MAb which recognized S4 were not neutralizing. Isolated S2-S4 and S3-S4 dimers bound to Chinese hamster ovary cells. These results indicate that the majority of critical epitopes which elicit neutralizing antibody are conformation dependent.